2019
DOI: 10.1021/acs.nanolett.9b00649
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Effect of an Electrostatic Gate with Angle-Resolved Photoemission Spectroscopy

Abstract: Electrostatic gating is pervasive in materials science, yet its effects on the electronic band structure of materials has never been revealed directly by angle-resolved photoemission spectroscopy (ARPES), the technique of choice to non-invasively probe the electronic band structure of a material. By means of a state-of-the-art ARPES setup with sub-micron spatial resolution, we have investigated a heterostructure composed of Bernal-stacked bilayer graphene (BLG) on hexagonal boron nitride and deposited on a gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…At high gate fields, Nguyen et al could also populate the Q valley in WSe 2 and demonstrate directly that its energy is slightly above the conduction band minimum at K. They further showed that this situation reverses in bi-and trilayer WSe 2 where the Q valley dips below the K valley, resulting in an indirect gap, consistent with prior results from optics [17]. Near simultaneous with the work of Nguyen et al, Joucken et al demonstrated in situ electrostatic gating of Bernal bilayer graphene during ARPES measurements [132]. Subsequently, in-operando ARPES studies have also been reported on monolayer graphene [133][134][135] and bilayer graphene with large twist angle [136,137].…”
Section: Reversible In-situ Electrostatic Gatingsupporting
confidence: 67%
“…At high gate fields, Nguyen et al could also populate the Q valley in WSe 2 and demonstrate directly that its energy is slightly above the conduction band minimum at K. They further showed that this situation reverses in bi-and trilayer WSe 2 where the Q valley dips below the K valley, resulting in an indirect gap, consistent with prior results from optics [17]. Near simultaneous with the work of Nguyen et al, Joucken et al demonstrated in situ electrostatic gating of Bernal bilayer graphene during ARPES measurements [132]. Subsequently, in-operando ARPES studies have also been reported on monolayer graphene [133][134][135] and bilayer graphene with large twist angle [136,137].…”
Section: Reversible In-situ Electrostatic Gatingsupporting
confidence: 67%
“…Similar approaches have only recently been demonstrated to lead to electrostatically tunable bands in single-layer graphene [32,33] and Bernal-stacked bilayer graphene. [34] An optical micrograph of the device is compared to a map of the photoemission intensity in Figure 1b,c, revealing the location of the twBLG flake between the top contacts used for grounding the flake. The data underlying the nanoARPES map is composed from a 4D dataset containing the (E, k, x, y)-dependent photoemission intensity and the image merely represents a projection of the E-and k-integrated intensity onto real space.…”
Section: Doi: 101002/adma202001656mentioning
confidence: 99%
“…The mesoscopic sizes and intrinsic inhomogeneities of such devices have posed the biggest challenges precluding conventional ARPES studies. These issues can be circumvented by using a microscopically focused beam of photons as demonstrated in recent microARPES experiments performed on 2D material based heterostructures and devices [20][21][22][23]. We apply this approach here to investigate the Coulomb interaction in graphene on hBN (graphene/hBN) at a relatively small interlayer twist angle of 2.0 • .…”
mentioning
confidence: 99%